2011
DOI: 10.1101/lm.2154311
|View full text |Cite
|
Sign up to set email alerts
|

The neural cell adhesion molecule-derived peptide FGL facilitates long-term plasticity in the dentate gyrus in vivo

Abstract: The neural cell adhesion molecule (NCAM) is known to play a role in developmental and structural processes but also in synaptic plasticity and memory of the adult animal. Recently, FGL, a NCAM mimetic peptide that binds to the Fibroblast Growth Factor Receptor 1 (FGFR-1), has been shown to have a beneficial impact on normal memory functioning, as well as to rescue some pathological cognitive impairments. Whether its facilitating impact may be mediated through promoting neuronal plasticity is not known. The pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…The DMS protocol we applied exerts high frequency oscillated stimulation in the brain of animal models and rescues the deficient LTP impaired by restraint stress in rats. On the other hand, LTP induction in the anesthetized rats increases neurogenesis in the dentate gyrus and FGFR activation by the neural cell adhesion molecule promotes neural progenitor proliferation by enhancing LTP [42,43]. Therefore, the study suggests that DMS administration may promote adult neurogenesis by inducing high frequency theta-burst stimulation and LTP in the hippocampus.…”
Section: Resultsmentioning
confidence: 99%
“…The DMS protocol we applied exerts high frequency oscillated stimulation in the brain of animal models and rescues the deficient LTP impaired by restraint stress in rats. On the other hand, LTP induction in the anesthetized rats increases neurogenesis in the dentate gyrus and FGFR activation by the neural cell adhesion molecule promotes neural progenitor proliferation by enhancing LTP [42,43]. Therefore, the study suggests that DMS administration may promote adult neurogenesis by inducing high frequency theta-burst stimulation and LTP in the hippocampus.…”
Section: Resultsmentioning
confidence: 99%
“…Rats showed memory improvement in water maze testing and fear conditioning paradigms immediately following ICV FGL administration, and in primary cultured rat hippocampal neurons, FGL promoted synapse formation and enhanced presynaptic function via FGFR1 activation [67]. Dallérac et al (2011) then demonstrated facilitation of LTP induction and maintenance in awake, behaving rats for up to 24 hours following ICV infusion of FGL, as well as altered neurogenesis associated with LTP [68]. …”
Section: Fgf2 and Neurodegeneration: Therapeutic Innovationsmentioning
confidence: 99%
“…Moreover, positive effects on neurogenesis in the dentate gyrus as well as neuroprotection in vitro have been described (Neiiendam et al 2004;Dallerac et al 2011). Our own previous data suggest a mobilization of endogenous NSC via systemic FGL-treatment under physiologic conditions in vivo .…”
Section: Discussionmentioning
confidence: 96%
“…Contrary to NCAM and due to its small size of only 15 amino acids, FGL readily crosses the blood-brain-barrier after systemic administration (Secher et al 2006;Klementiev et al 2007;Chen et al 2010). FGL has been shown to enhance spatial learning and memory, probably by facilitating plasticity in the hippocampus, and it exerts anti-inflammatory effects upon glia cells (Dallerac et al 2011, Knafo et al, 2012, Cox et al, 2013. We recently showed that FGL both mobilizes endogenous neural stem cells (NSC) and enhances the generation of oligodendrocytes in vitro .…”
Section: Introductionmentioning
confidence: 96%